Moderate caloric restriction during gestation in rats alters adipose tissue sympathetic innervation and later adiposity in offspring. - Ana Paula García; Mariona Palou; Juana Sánchez; Teresa Priego; Andreu Palou; Catalina Picó (PLoS ONE, 2011)
Maternal prenatal undernutrition predisposes offspring to higher adiposity in adulthood. Mechanisms involved in these programming effects, apart from those described in central nervous system development, have not been established. Here we aimed to evaluate whether moderate caloric restriction during early pregnancy in rats affects white adipose tissue (WAT) sympathetic innervation in the offspring, and its relationship with adiposity development. For this purpose, inguinal and retroperitoneal WAT (iWAT and rpWAT, respectively) were analyzed in male and female offspring of control and 20% caloric-restricted (from 1-12 d of pregnancy) (CR) dams. Body weight (BW), the weight, DNA-content, morphological features and the immunoreactive tyrosine hydroxylase and Neuropeptide Y area (TH+ and NPY+ respectively, performed by immunohistochemistry) of both fat depots, were studied at 25 d and 6 m of age, the latter after 2 m exposure to high fat diet. At 6 m of life, CR males but not females, exhibited greater BW, and greater weight and total DNA-content in iWAT, without changes in adipocytes size, suggesting the development of hyperplasia in this depot. However, in rpWAT, CR males but not females, showed larger adipocyte diameter, with no changes in DNA-content, suggesting the development of hypertrophy. These parameters were not different between control and CR animals at the age of 25 d. In iWAT, both at 25 d and 6 m, CR males but not females, showed lower TH(+) and NPY(+), suggesting lower sympathetic innervation in CR males compared to control males. In rpWAT, at 6 m but not at 25 d, CR males but not females, showed lower TH(+) and NPY(+). Thus, the effects of caloric restriction during gestation on later adiposity and on the differences in the adult phenotype between internal and subcutaneous fat depots in the male offspring may be associated in part with specific alterations in sympathetic innervation, which may impact on WAT architecture.